Blended learning – integrating E-learning with traditional learning methods in teaching basic medical science - J.G. Bagi (Al Ameen Journal of Medical Sciences, 2014)
Background: Blended learning includes an integration of face to face classroom learning with technology enhanced online material. It provides the convenience, speed and cost effectiveness of e-learning with the personal touch of traditional learning. Objective: The objective of the present study was to assess the effectiveness of a combination of e-learning module and traditional teaching (Blended learning) as compared to traditional teaching alone to teach acid base homeostasis to Phase I MBBS students. Method: The entire batch of 200 students who had exposure to traditional lecture teaching on acid base homeostasis was randomly divided two batches and the integrated e-learning module was implemented for 100 students of MBBS Phase I (200 students). The mean scores of both the groups were compared using unpaired t-test. Result: The mean performance scores of the students of blended group was statistically (p < 0.05) significant as compared to that of the students who received only traditional teaching. Conclusion: The concept of understanding the complex contents like acid- base homeostasis and its application on patient care was better among the group of students who had exposure to blended learning than those, only to traditional class room learning.